Investigating the self-management model the Islamic perspective - Abd Rashid, Adnan (Leena and Luna International, Oyama, Japan, 2013)
Islam states that the creation of man is a composite of the material and spiritual. This is based on the creation of Adam who was the beginning of man on earth from a material thing. Because of that, man is inseparable during his life from material provisions in order to survive particularly the tendencies to obtain material benefits and satisfy basic instincts in this world are very high. The Qur’anic verses also explain that Allah has breathed into Adam His Spirit which means that the potential to be good was implanted into him. As long as man preserves his spirit pure he may maintain good moral values. This atmosphere signifies that man’s dealing with material things would coincide with the spiritual values. So that he can manage his greedy, selfishness, pride and prone to neither transgress in worldly matters and spiritually nor deny all material pleasures. In this way man as a potential leader may be able to manage his selfish personality with other people and the living system in society. This concept paper attempts to discuss the efforts on how to manage man’s selfishness by monitoring spiritual aspects with the need of materials based on the Qur’an and Sunnah.